The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/shk.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Severe Burn Injury Induces Thermogenically Functional Mitochondria in Murine White Adipose Tissue

Abstract: Chronic cold exposure induces functionally thermogenic mitochondria in the inguinal white adipose tissue (iWAT) of mice. Whether this response occurs in pathophysiological states remains unclear. The purpose of this study was to determine the impact of severe burn trauma on iWAT mitochondrial function in mice. Male balb-c mice (10–12 weeks) received full-thickness scald burns to ~30% of the body surface area. iWAT was harvested from mice at 1, 4, 10, 20, and 40 days post injury. Total and uncoupling protein 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
(56 reference statements)
4
32
1
Order By: Relevance
“…B panels i–vi), suggesting progressive browning of sWAT in response to burn trauma. This is in line with our findings in rodents, showing a gradual change in sWAT morphology after burn injury (Porter et al, 2015). Finally, transmission electron microscopy confirmed the presence of adipocytes with an abundance of small (0.5–1μm) lipid droplets and numerous electron-dense, rod-shaped mitochondria in the sWAT from burn patients (Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…B panels i–vi), suggesting progressive browning of sWAT in response to burn trauma. This is in line with our findings in rodents, showing a gradual change in sWAT morphology after burn injury (Porter et al, 2015). Finally, transmission electron microscopy confirmed the presence of adipocytes with an abundance of small (0.5–1μm) lipid droplets and numerous electron-dense, rod-shaped mitochondria in the sWAT from burn patients (Fig.…”
Section: Resultssupporting
confidence: 93%
“…3B). We found that CS activity significantly increased by 130% (38±11 vs. 89±16 nmol/g/sec) in the two weeks that patients were followed (P<0.01), which is agreement with our recent data showing greater CS activity in sWAT of burned mice (Porter et al, 2015). In addition to our morphological data (Fig 1C), these data provide further evidence that mitochondrial biogenesis occurs in sWAT following burn injury, similar to that which occurs in murine sWAT in response to chronic cold exposure (Shabalina et al, 2013).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We used a murine model of full-thickness burn trauma in the current study [1518]. Similar to humans, hypermetabolism has been documented in similar murine models of burn trauma [19].…”
Section: Methodsmentioning
confidence: 99%